La gestión para la construcción - Narváez Puentes, Olga Tatiana (Universidad Antonio Nariño, 2022)
A large percentage of students, technicians, professionals with little experience, foreign professionals living in the country, all those who surround the branch of architecture in the city of Neiva have shown over time and circumstances that they are not competent at the level national in the project organization regarding construction license processes; Therefore, it is proposed to obtain an important guiding instrument for the organization, which serves as support with the basic information necessary centralized with the step by step for the realization of the objective, which functions as a manual for the fulfillment of the plan with management, quality , time and costs required in a project.